When play at work can foster harassment-based norms: exploring moral disengagement during social play - Samnani, Al-Karim (Journal of business ethics, 2025)
Play at work has received burgeoning interest in recent years. This research has largely focused on its positive outcomes despite fragmented evidence that play at work can produce behaviors such as clowning, teasing, pranking, and telling jokes at others’ expense. This manuscript constructs theory highlighting the evolving nature of disclosures in explaining how social play can produce harassment norms. This theory is distilled into four broad stages. In the first stage, employees participating in social play develop greater personal comfort with their co-workers through reduced work/non-work boundaries, greater psychological safety, and increased psychosocial resources. In the second stage, employees who develop personal comfort "open up" as they loosen self-control and engage in mutual self-disclosures, particularly with those who are perceived to share similarities. In the third stage, employees who have high implicit bias make more risky disclosures by expressing biased views as jokes during play. In the fourth stage, contagion processes occur when co-workers react in perceivably supportive ways, such as laughing and repeating jokes. This model illustrates how social play can lead employees to morally disengage by using the context of play to morally justify the expression of their implicit biases, which enables harassment to go unchecked and become reinforced.